2021
DOI: 10.1038/s41589-021-00817-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional processing of an unnatural base pair by eukaryotic RNA polymerase II

Abstract: The development of unnatural base pairs (UBPs) has greatly increased the information storage capacity of DNA, allowing for transcription of unnatural RNA by the heterologously expressed T7 RNA polymerase (RNAP) in Escherichia coli. However, little is known about how UBPs are transcribed by cellular RNA polymerases. Here, we investigate how synthetic unnatural nucleotides, NaM and TPT3, are recognized by eukaryotic RNA polymerase II (Pol II) and found that Pol II is able to selectively re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 60 publications
(88 reference statements)
0
19
1
Order By: Relevance
“…In another approach, with CSR method, Holliger and co-workers evolved a Taq/Tth/Tfl DNAP mutant, 5D4, for the ability of forming and extending other selfpairs of hydrophobic nucleobase analogs, including 5NI and 5NIC 93 . The transcription of some of these UBPs has been demonstrated with several well-studied RNAPs, including T7 RNAP and eukaryotic RNAP II 30,151 suggested that E. coli RNAP could also transcribe DNA containing some of these investigated for the activity of incorporating 2'-modified nucleotides 159 . T7 RNAP mutant Y639F has been found to be able to use various 2'-substituted-NTPs, including dNTPs, 2'-F-dNTPs, and 2'-Am-dNTPs, as substrates during transcription 168,169 , and mutant with one more mutation, T7 RNAP (Y639F, H784A), displayed higher activity against NTPs with bulkier 2'-substitutions, including 2'-OMe and 2'-Az 170 .…”
Section: Rsc Chemical Biology Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…In another approach, with CSR method, Holliger and co-workers evolved a Taq/Tth/Tfl DNAP mutant, 5D4, for the ability of forming and extending other selfpairs of hydrophobic nucleobase analogs, including 5NI and 5NIC 93 . The transcription of some of these UBPs has been demonstrated with several well-studied RNAPs, including T7 RNAP and eukaryotic RNAP II 30,151 suggested that E. coli RNAP could also transcribe DNA containing some of these investigated for the activity of incorporating 2'-modified nucleotides 159 . T7 RNAP mutant Y639F has been found to be able to use various 2'-substituted-NTPs, including dNTPs, 2'-F-dNTPs, and 2'-Am-dNTPs, as substrates during transcription 168,169 , and mutant with one more mutation, T7 RNAP (Y639F, H784A), displayed higher activity against NTPs with bulkier 2'-substitutions, including 2'-OMe and 2'-Az 170 .…”
Section: Rsc Chemical Biology Accepted Manuscriptmentioning
confidence: 99%
“…93 The transcription of some of these UBPs has been demonstrated with several well-studied RNAPs, including T7 RNAP and eukaryotic RNAP II. 30,151 Recent in vivo experiments suggested that E . coli RNAP could also transcribe DNA containing some of these UBPs.…”
Section: Polymerase Engineering For the Synthesis Reverse Transcripti...mentioning
confidence: 99%
See 1 more Smart Citation
“…This might be because the variable codon performance is the total output of the sequence-dependent translation efficiency, although the recognition of the codon-anticodon interaction might differ in eukaryotic cells ( Zhou et al, 2019 ). They are currently exploring the recognition of the NaM–TPT3 pair by the multi-subunit E. coli RNA polymerase II, as compared to the single-subunit T7 RNA polymerase, to create next generation SSOs ( Hashimoto et al, 2021 ; Oh et al, 2021 ).…”
Section: Genetic Code Expansion Using Ubp Systemsmentioning
confidence: 99%
“…12 In vitro kinetic, structural, and simulation studies suggested that eukaryotic multisubunit RNA polymerases recognize the UBP with reasonable efficiency and fidelity when dTPT3 is in the template strand, but less so with dNaM in the template strand. 13 However, it was unclear whether this was also the case with the E. coli enzyme and moreover whether transcription might be altered in an in vivo environment due to for example proofreading, 14,15 transcription−translation coupling, attenuation, or anti-termination mechanisms. 16 Thus, exploring whether the endogenous E. coli RNA polymerase is able to transcribe DNA containing the UBP in the SSO would not only provide a unique means to explore the substrate scope of this important enzyme in vivo but also could eventually provide access to mechanisms that might further optimize the SSO.…”
mentioning
confidence: 99%